PENGARUH KARAKTERISTIK PEKERJAAN DAN PEMBERDAYAAN TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL (Studi Pada Politeknik Ilmu Pelayaran Semarang) - Heriyawan, Mohammad Sapta; Setyowati, Widhy (Proceeding SENDI_U, 2015)
This Research have a purpose to explain the influence job characteristic and empowerment onemployees performance mediation by Organizational Commitment at office of SemarangMerchant Marine Polytechnic. Research population is public servant of Civil at SemarangMerchant Marine Polytechnic, while sample use the technique of purposive sampling. Methoddata collecting by using quesioner which passed to a responder. Examination to researchinstrument done with the validity test ( analyse the factor) and test the reliabilitas with thecoefficient alpha of appliance to statistic test by multiple regression analysis regresi, test the t, testR2 and mediation test. Result of research indicate that the Job characteristic have an effect onpositive and significant to organizational commitment. Empowerment have an effect is positiveand significant to organizational commitment, Job characteristic have an effect on the positivebut not significant to employees performance, Empowerment have an effect is positive andsignificant to employees performance, while Organizational Commitment have an effect is positiveand significant on employees performance.KeywordS: Job Characteristic, Empowerment, Organizational Commitment, EmployeesPerformance.